The Impact Of Psak 72 Implementation On Financial Performance In The Pandemic Time Covid-19 (Empirical Study On Real Estate Companies Registered In Indonesia Stock Exchange) - Duwi Rahayu Rahayu; Imelda Dian Rahmawati; Dina Dwi Oktavia Rini (SENTRALISASI, 2021)
The purpose of this study is to examine the impact of the implementation of PSAK 72 on financial performance during the Covid-19 pandemic (empirical study of real estate companies listed on the Indonesian stock exchange). This research is a quantitative research, where the data used are secondary data in the form of financial statements of real estate companies. The sample of this study is a real estate company that provides periodic financial reports on the Indonesia Stock Exchange in 2019 and the second quarter of 2020 with a total of 46 sample companies. The results of the study indicate that PSAK 72 has a significant negative effect on the liquidity ratio, profitability ratio, activity ratio, and market ratio, while the implementation of PSAK 72 has no significant effect on the solvency ratio. This show, although the implementation of PSAK 72 has had a significant negative effect, companies have started to prepare for the implementation of PSAK 72 by conducting evaluations, adaptations and training for employees before actually implementing PSAK 72. The meaning of not fully implementing PSAK 72 has a negative impact on real estate company earnings, because the implementation of these standards was also followed by the Covid-19 pandemic which also resulted in a decrease in income for companies.